Involvement of Grower, Supplier and Product Innovation in Determining the Business Performance of Malaysian Poultry Industry: Moderating Role of Management Skills - Sinaga, Obsatar; Novianto, Robertus; Apriwandi, Apriwandi; Shaleh, Khairul; Isa, Azizan Mohamed (ExcelingTech, 2019)
The study investigates the supply chain actors of poultry industry in Malaysian context. Involvement of grower and supplier has significant impact on supply chain and ultimately success of business while improving the performance of business. Current study entails the important actors of supply chain found crucial in poultry industry, these factors include involvement of grower, supplier and innovation of product to increase quality and enhance performance. The broiler industry has increased rapidly and expected to grow higher in future; to meet the increasing demand supply chain must be effective and responsive towards the market challenges. The research found that involvement of grower has significant impact on business performance, supplier also found to significant along with innovation capability influence business performance in poultry industry. In previous researches managerial skills are ignored but the study explains the moderating effect of management in determining the performance while considering the supply chain actor of poultry industry of Malaysia.